1987
DOI: 10.1002/food.19870310580
|View full text |Cite
|
Sign up to set email alerts
|

The minipig as a model in gnotobiology

Abstract: Due to its close physiological and morphological resemblance to man, the pig occupies an important position in biomedical research. The minipig lends itself particularly well to germfree research. It is easy to deliver, maintain, and utilize in isolators. The colostrum-free, newborn germfree piglet lacking passively obtained antibodies is of an exclusive use if distinguishing the factors of natural and adaptive immunity is needed. It fits also well in studies investigating the earliest mechanisms of antibody s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…This crucial development provided tools to study basic questions about the host-microbiota interaction using various animal models. [38][39][40][41][42][43][44] We have shown that microbial colonization of animals living in germ-free conditions results in an increase in immunoglobulin levels, the production of specific antibodies, substantial changes in mucosal-associated lymphocyte tissues and cell populations, changes in migration patterns and increases in the systemic immunological capacity. 35,40,42,43 In the early postnatal period, components of the normal microbiota induce a transient physiological inflammatory response in the gut associated with enlargement of the mucosal-associated lymphatic tissue and increases in its cellularity.…”
Section: The Role Of the Microbiota In Postnatal Development Of Innatmentioning
confidence: 99%
“…This crucial development provided tools to study basic questions about the host-microbiota interaction using various animal models. [38][39][40][41][42][43][44] We have shown that microbial colonization of animals living in germ-free conditions results in an increase in immunoglobulin levels, the production of specific antibodies, substantial changes in mucosal-associated lymphocyte tissues and cell populations, changes in migration patterns and increases in the systemic immunological capacity. 35,40,42,43 In the early postnatal period, components of the normal microbiota induce a transient physiological inflammatory response in the gut associated with enlargement of the mucosal-associated lymphatic tissue and increases in its cellularity.…”
Section: The Role Of the Microbiota In Postnatal Development Of Innatmentioning
confidence: 99%
“…Colostrum-deprived germ-free piglets were obtained by hysterectomy under halothane anaesthesia on the 112th day of gestation. Piglets were reared in positive-pressure microbiologically controlled fibreglass isolators and fed to satiety with autoclave-sterilized milk diet supplemented with minerals and vitamins [28]. Piglets were checked for sterility two times a week and on the day of euthanasia by culturing rectal swabs aerobically and anaerobically and by staining methods [29].…”
Section: Animalsmentioning
confidence: 99%
“…Germ-free piglets of miniature Minnesota-derived pig breed [94] (Animal Research Institute, Kostelec nad Orlici, Czechia) were obtained by hysterectomy under isoflurane anesthesia at expected term, reared in positive-pressure fiber-glass isolators, fed via nipple by cow's milk-based formula (Mlekarna Hlinsko, Hlinsko, Czechia), and microbiologically checked, as described in detail elsewhere [45]. Each piglet group was created from three independent hysterectomies.…”
Section: Gnotobiotic Pigletsmentioning
confidence: 99%